OPTIMALISASI HASIL BELAJAR PENDIDIKAN JASMANI MATERI SOFTBALL MELALUI MEDIA VIDEO VISUAL TERHADAP SISWA SMA NEGERI UNGGUL ACEH TIMUR - Erwin (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2021)
This research was conducted at East Aceh Superior Senior High School which aims to further optimize the learning outcomes of class XI IPS students in Physical Education lessons through Visual Video Media. The research subjects were all students of class XI IPS which may be 27 students. In collecting data, researchers used instruments or data analysis techniques in the form of 10 multiple choice test items and an observation sheet. After the data was collected, the researcher managed and analyzed the data by comparing the test results and observations from the initial conditions of action one (first cycle) and the second. The results showed an increase in student completeness in the first cycle to 78% (21 students) from the initial condition which was only 44% (12 students), and at the end of the second cycle completeness increased again to 93% (25 students). Thus it is abbreviated that the application of video improves physical education learning outcomes more optimally in class XI IPS for the first semester of the 2019/2020 academic year at East Aceh Superior Senior High School.